Pengaruh Kompetensi Dan Komitmen Profesional terhadap Motivasi Kerja Auditor ( Studi Empiris Pada Inspektorat Kabupaten Aceh Utara ) - Murhaban Murhaban (Jurnal Dinamika Akuntansi dan Bisnis, 2014)
This study aims to determine whether the professional competence and commitment affect the auditor's working motivation at the Inspectorate of North Aceh district. The research method in this study is causal research design with the auditors of Inspectorate of North Aceh district as samples. This study was conducted in 2011. Data used is primary data that were obtained from questionnaires and distributed directly to the auditors in North Aceh district Inspectorate. The data analyzed in this study were compiled from questionnaire respondents regarding the competence, commitment and motivation of professional auditors. The method of analysis in this study is a qualitative analysis method by testing the quality of the data and classical assumptions testing and then the data will analysis by multiple linear regressions with t-Test and F Test. The results showed that the competence does not give effect partially on Auditor’s working motivation in North Aceh District Inspectorate, while the profession 's commitment partially has an effect on working motivation to auditors in North Aceh District Inspectorate. Simultaneously, competence and professional commitment has an effect working motivation of auditors in North Aceh District Inspectorate.